Defend Clandestine Rated Multi-keyword Search for Multi-Proprietors in Cloud Computing - Vanishree, KA; Santhiya, C; Chandrasekaran, MK (International Journal of Computer Sciences and Engineering, 2025)
Due to the escalating popularity of cloud computing, more and more data owners are encouraged to outsource their data to cloud servers for great convenience and scaled-down the cost in data management. For privacy concerns, secure searches over encrypted cloud data have motivated numerous research works under the solitary owner model. However, most cloud servers in practice do not just serve single owner; instead, they support multiple owners to share their profits fetched by cloud computing. In our proposed scheme which is deals with Defend Clandestine rated Multi-keyword Search in a Multi-proprietor model (DCMSM). To activate cloud servers to perform secure search without knowing the actual data of both keywords and trapdoors, we methodically build a newfangled secure search protocol. We propose another technique as distinct Additive Order and Privacy Preserving Function family for the purpose of rank the search results and preserve the privacy of appositeness scores between keywords and files. By introducing a modish dynamic secret key generation protocol and a novel data user authentication protocol to prevent the attackers from intruding secret keys and concealing the legal data users submitting searches. Additionally, DCMSM supports efficient data user invocation. Comprehensive experiments on real-world datasets confirm the efficaciousness and efficiency of DCMSM.